Possibilities of ultrasonic diagnosis in traumatology and orthopedics - Shevchenko, Stanislav; Yakovenko, Inna; Martyuk, Victor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article describes possible applications of the technique of ultrasonic examination for diagnosing the state of the locomotor system in children.